2017
DOI: 10.1063/1.4989441
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of soft mechanical metamaterials: Independent tailoring of elastic properties with randomness

Abstract: The elastic properties of mechanical metamaterials are direct functions of their topological designs. Rational design approaches based on computational models could, therefore, be used to devise topological designs that result in the desired properties. It is of particular importance to independently tailor the elastic modulus and Poisson's ratio of metamaterials. Here, we present patterned randomness as a strategy for independent tailoring of both properties. Soft mechanical metamaterials incorporating variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 18 publications
(16 reference statements)
0
42
0
Order By: Relevance
“…Recent studies have shown that rational distribution of auxetic and conventional could give rise to novel properties and functionalities. 29 We considered five graded designs to demonstrate the presented "action-at-a-distance" concept, namely linear, radial gradient negative to positive (NTP), radial gradient positive to negative (PTN), checkered, and striped (Fig. 1).…”
Section: © 2018 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…Recent studies have shown that rational distribution of auxetic and conventional could give rise to novel properties and functionalities. 29 We considered five graded designs to demonstrate the presented "action-at-a-distance" concept, namely linear, radial gradient negative to positive (NTP), radial gradient positive to negative (PTN), checkered, and striped (Fig. 1).…”
Section: © 2018 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…Random elastic networks are widely studied [36][37][38] , but there are still large gaps between theoretical investigations and practical purposes such as real solid materials. Mechanical meta-materials with increasing degree of disorder are just emerging [39][40][41][42][43] . Whether disorder is merely the price to pay for self-assembly or whether it provides some advantage is still an open issue.The structural behaviour of lattice based metamaterials, made up of beams with non-hinged nodes, is generally divided into two regimes: stretching-dominated and bending-dominated 44 .…”
mentioning
confidence: 99%
“…17 While batch-size-indifference directly translates to the feasibility of producing patient-specific biomaterials, implants, and surgical instruments [18][19][20][21][22] that exactly match the complex and highly variable anatomy 23 of individual patients, complexity-for-free enables designers to use complex geometries that give rise to favorable properties and advanced functionalities. [24][25][26][27][28][29] One particularly useful class of geometrically complex biomaterials is the class of topologically ordered porous biomaterials that are designed by repeating one or more regular unit cells in different spatial directions to create a lattice (cellular) structure (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%